Get to the bridge and I will help you to cross': Merit, personal connections, and money as routes to success in Nigerian higher education - Chris Willott (University of Bath, Centre for Development Studies (CDS), 2009)
The state is acknowledged as the central actor in development, and there are numerous studies on African states and their relationships to societies. However, the vast majority of these studies focus on the highest echelons of politics and policymaking, with very few dedicated to how the state is experienced and lived by its users. This literature tends therefore to be abstract. Furthermore, much literature, particularly that stressing the neopatrimonial character of African states, examines states through the prism of Weberian logic and suggests that, because states do not conform to a rational-legal ideal, they must therefore be deficient or dysfunctional. This literature therefore tends to be quite normative. This paper offers a less normative and abstract understanding of the state in everyday action, through analysis of the workings of the Nigerian higher education sector. It draws on primary data collected through ethnographic methods to analyse how service providers and users of a university in south-eastern Nigeria negotiate their passage into, and through, a highly complex and flexible system. The paper argues that achieving success in Nigerian higher education is dependent on a combination of merit, personal connections and money. While all students enter the university on the basis of merit (locally referred to as 'getting to the bridge'), personal connections and money are crucial influences. The relative importance of the latter is stronger among poorer performing students. Furthermore, the paper will demonstrate that amongst academic staff, personal connections to influential people and factions are the most important factors influencing success. The notion of 'get to the bridge and I will help you to cross' is also important for staff as official credentials are a necessary but not sufficient criteria for academic success. Strong personal connections play a key and decisive role. The case presented in the paper offers an important corrective to the rather abstract and normative ideas that underpin the theory of the African neopatrimonial state. It argues that a better understanding of the state requires a stronger focus on the routine and real experiences of service providers and users, as well as on their everyday interactions.
Keywords: 330; Bildungschancen; Hochschule; Soziale Beziehungen; Bildungsfinanzierung; Nigeria